(untitled) (Journal of the Bangladesh Agricultural University, 2012)
A total of 270 native chickens of two months of age were reared up to their six months of age under three densities D1, D2 and D3 (0.186, 0.279 and 0.372 m2/bird) and three flock sizes F1, F2 and F3 (20, 30 and 40 birds/flock) to find out the effect of density (D) and flock size (F) on the growth performance of native chicken under intensive system of management. Body weight gain and feed intake were higher (5.62 & 5.39 and 50.17 & 50.42) and feed conversion ratio and mortality were the lower (9.48 & 10.02) in D2 unit and (12.01 & 13.05) in F2 unit. On the other hand, body weight gain was the lowest (4.81) in D3 unit. Feed intake was the lowest (49.25) in D1 unit with the highest (11.70) FCR value. Body weight gain was found to be the lowest (4.81) in F3 unit but its FCR and mortality rate were the highest (11.25 and 17.71). Feed intake was observed to be the lowest (49.17) in the F1 unit. Considering the growth performance of native chickens under different densities and flock sizes, it could be concluded that flock size F2 (30 birds/flock) performed better at the density level D2 (0.279 m2/bird) than other densities and other flock sizes. DOI: http://dx.doi.org/10.3329/jbau.v10i1.12040 J. Bangladesh Agril. Univ. 10(1): 5559, 2012